2021
DOI: 10.1111/plb.13277
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous trehalose protects photosystem II by promoting cyclic electron flow under heat and drought stresses in winter wheat

Abstract: Drought and rising global temperatures are important factors that reduce wheat production. Trehalose protects the reaction centres and improves photosystem II (PSII) activity under diverse stress conditions. However, the underlying mechanism remains unknown. Cyclic electron flow (CEF) plays an important role in protecting PSII under environmental stresses. Our study focused on the effects of exogenous trehalose on the activity of PSII, D1 protein content, plastoquinone (PQ) pool and ATP synthase activity in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This indicated that trehalose pretreatment could protect the protein secondary structures of PSII reaction center complex, which was similar to a previous report involving spray dried poly-L-lysine (Mauerer & Lee 2006). The protective effect of trehalose on the PSII reaction center complex may be due to the stimulation of circulating electron flow (Luo et al 2021).…”
Section: O N L I N E F I R S Tsupporting
confidence: 89%
“…This indicated that trehalose pretreatment could protect the protein secondary structures of PSII reaction center complex, which was similar to a previous report involving spray dried poly-L-lysine (Mauerer & Lee 2006). The protective effect of trehalose on the PSII reaction center complex may be due to the stimulation of circulating electron flow (Luo et al 2021).…”
Section: O N L I N E F I R S Tsupporting
confidence: 89%
“…Excessive light energy can, under stress conditions, contribute to ROS production within chloroplasts that can damage both PSII and PSI. CEF-PSI can effectively protect against photodamage, and many prior reports have demonstrated that CEF can shield PSI from stressors including cold [ 67 ], heat [ 68 ], drought [ 69 ], and other adverse conditions [ 70 ]. By oxidizing PSI acceptor-side components through the recycling of electrons from PSI to the plastoquinone (PQ) pool and Cyt b6/f, CEF can mitigate acceptor-side reduction [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The P700 signal was determined during single-turn saturation pulse [ST, 50 ms, plastoquinone (PQ) pools being oxidized] followed by multiple-turn saturation pulse (MT, 50 ms, PQ pools fully reduced) in the presence of far-red background light ( Savitch et al, 2001 ; Luo et al, 2021 ). The complementary area between the P700 oxidation curve after a single-turnover and multiple-turnover excitations and the stationary level of P700 + under far-red light represents the single-turn and multiple-turn areas, respectively.…”
Section: Methodsmentioning
confidence: 99%